Unveiling the BPF9 Isolate as a Potential of Phosphate-Solubilizing Bacteria Through In Vitro Characterization - Devanda Ayu Lidya Permata Putri; Guruh Mayka Putra; Laudy Arrisa Arumsari Sahana; Intan Nirmalasari (Acta Solum, 2025)
The increasing demand for food has driven agricultural intensification, particularly through the use of phosphate fertilizers. However, phosphorus uptake efficiency by plants remains low due to its predominance in insoluble forms in the soil. One promising alternative is the use of phosphate-solubilizing bacteria (PSB). This study aimed to evaluate the solubilization potential of the BPF9 isolate through qualitative and quantitative assays, as well as growth curve profiling. The research was conducted at the Soil and Environmental Biotechnology Laboratory, IPB University. Qualitative phosphate solubilization was assessed on Pikovskaya agar by measuring halo zone formation to calculate the solubilization index (SI). Quantitative analysis was carried out using spectrophotometry at 660 nm. The bacterial growth curve was analyzed using the haemocytometer method. Results showed that BPF9 had a solubilization index of 2.0 (moderate category) and was able to solubilize phosphate up to 128.5 ppm, which is considered highly efficient. The growth curve indicated that BPF9 entered the exponential phase at 26 hours and reached its maximum population at 42 hours. These findings indicate that BPF9 possesses strong phosphate-solubilizing capability and stable growth characteristics, making it a promising candidate for biofertilizer development.